A ∼6,600 year history of vegetation changes and sediment infill of the Moulay Bousselham Lagoon, Atlantic Morocco - (:unkn) unknown (My University, 2025)
The Moulay Bousselham Lagoon, composed of two parts, Merja Kahla and Merja Zerga, is one of the largest tidal lagoons on the Atlantic coast of NW Africa. Designated as a Ramsar Site, the Moulay Bousselham Lagoon has been identified as a significant carbon sink. Our research aims are to reconstruct regional vegetation changes and lagoonal infill history. The sedimentary infill was studied using three 3-3.5 m long cores dating to the Middle and Late Holocene. The main palaeoenvironmental proxies included sedimentology, foraminiferal analysis and palynology. Apart from a basal sandy unit and a later and likely short-lived one, the lagoonal deposits mainly consist of sandy muds with about 10 % organic matter. Our results reveal an environmental transformation from an open lagoon to a restricted one at c. 6600-6100 cal yr BP, coinciding with rising global sea level. While in Merja Zerga grass meadows developed, Merja Kahla, closer to the inlet, was covered by salt marshes. The location of this coastal lagoon remained relatively stable since then, as reshaping is limited by an uplifting barrier consisting of a resistant calcarenite ridge. The Drader River and, since 1953 the Nador Canal, contribute sediment to the lagoon. Sedimentation rates range from 0.01 to 0.09 cm/yr, with a recent ten-fold increase mostly owing to enhanced anthropogenic erosion in the catchments. Despite this, the accommodation space is maintained due to tectonic subsidence along the lagoonal basin and the lower stretch of the river, and the role of carbon sink increases over time. The reconstructed vegetation history indicates a decline of the cork oak forest. An ancient human presence is recorded dating back to at least the Neolithic period and suggests the likelihood of ancient Olea usage. This contrasts with much later modifications in vegetation cover in the nearby Rif Mountains.
Keywords: African Research